2023
DOI: 10.1111/1750-3841.16625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oven roasting on major chemical components in cereals and its modulation on flour‐based products quality

Abstract: Oven roasting (OR) could induce hierarchical structural changes in starch, which is fundamental for altering the pasting and hydration properties of cereal flour. OR makes proteins denatured and peptide chains unraveled or rearranged. OR could alter compositions of cereal lipids and minerals. Although OR may degrade phenolics, their release from bound forms is predominant when mild/moderate conditions are exerted. Hence, some OR‐modified cereals even exhibit many physiological functions, such as anti‐diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
0
4
0
Order By: Relevance
“…These included 20 phenolic acids and aldehydes, 8 flavan-3-ols and 6 flavone glycosides ( Table 4 ). Phenolic compounds (PCs) of barley grain can be found free, conjugated with sugars via glycosidic bonds, or covalently linked to components of the cell wall ( Li, Wang, Liu, Hong, & Zheng, 2023 ). Table 4 shows the PCs organized by main families in barley grain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These included 20 phenolic acids and aldehydes, 8 flavan-3-ols and 6 flavone glycosides ( Table 4 ). Phenolic compounds (PCs) of barley grain can be found free, conjugated with sugars via glycosidic bonds, or covalently linked to components of the cell wall ( Li, Wang, Liu, Hong, & Zheng, 2023 ). Table 4 shows the PCs organized by main families in barley grain.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that phenolic acids are comparatively more stable or resistant to roasting at 188 °C than flavonoids. The susceptibility to high temperatures varies with different classes of phenolic compounds due to differences in their chemical structures ( Li et al, 2023 ). Previous studies have also found that flavonoids are more sensitive to heat and their degradation is observed at lower temperatures around 120 °C ( Antony & Farid, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations